2021
DOI: 10.1111/jth.15154
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia exacerbates ischemic stroke outcome independent of platelet glucose uptake

Abstract: Objective Hyperglycemia is a common comorbidity for ischemic stroke and is associated with worsened neurological outcomes. Platelets are central mediators of ischemic stroke and hyperglycemia mediates platelet hyperactivity. In this study, we investigated the contribution of platelet glucose metabolism to ischemic stroke. Methods Mice lacking both Glut1 and Glut3 specifically in platelets (DKO) and their littermate controls (WT) were subjected to 1‐hour transient middle cerebral artery occlusion under normogly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…Neutrophils were resuspended to a concentration of 1 × 10 6 cells/mL in Medium 199. Platelets were purified as described previously ( 66 , 67 ), resuspended to 1 × 10 8 cells/mL in Medium 199, and activated with 50 ng/mL convulxin (sc-202554, Santa Cruz Biotechnology) for 15 minutes. Activated platelets and neutrophils were incubated at a 100:1 ratio to induce NETs for 2.5 hours at 37°C in 5% CO 2 /95% air.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Neutrophils were resuspended to a concentration of 1 × 10 6 cells/mL in Medium 199. Platelets were purified as described previously ( 66 , 67 ), resuspended to 1 × 10 8 cells/mL in Medium 199, and activated with 50 ng/mL convulxin (sc-202554, Santa Cruz Biotechnology) for 15 minutes. Activated platelets and neutrophils were incubated at a 100:1 ratio to induce NETs for 2.5 hours at 37°C in 5% CO 2 /95% air.…”
Section: Methodsmentioning
confidence: 99%
“…Transient middle cerebral artery occlusion (tMCAO) was performed as described previously ( 67 , 68 ). Briefly, occlusion of the right MCA was achieved by insertion of a standardized monofilament (Doccol Corp.) via the right internal carotid artery to occlude the origin of the right MCA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperglycemia plays an important role in early reperfusion by increasing blood–brain barrier permeability and extravasation of neutrophils within the infarcted area, leading to worse clinical outcomes [ 32 , 33 ]. Recent studies reported that high blood glucose may be related to a lower cerebral glucose level and contributes to procoagulant platelet formation, which would increase the severity of ischemia [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The treatment delay develops neuronal cell death to induce adverse outcomes, such as vision problems, paralysis in the limbs, dizziness, confusion, and coordination loss due to blockage in the brain areas. Furthermore, post-stroke hyperglycemia exacerbates the post-stroke outcomes by aggravating neuronal cell death through promoting procoagulant platelet formation and reducing cerebral blood flow [3,4]. Therefore, hyperglycemia, dyslipidemia, and hypertension need to be controlled to reduce stroke events and alleviate post-stroke consequences.…”
Section: Introductionmentioning
confidence: 99%